2021
DOI: 10.1016/j.xcrm.2021.100277
|View full text |Cite
|
Sign up to set email alerts
|

Integrative metabolomics and transcriptomics identifies itaconate as an adjunct therapy to treat ocular bacterial infection

Abstract: Integrative metabolomics and transcriptomics identifies itaconate as an adjunct therapy to treat ocular bacterial infection Graphical abstract Highlights d Bacterial infection increases Irg1 and itaconate levels in the eye d Irg1 and Nrf2 deficiency exacerbates intraocular bacterial infection d Itaconate potentiates antioxidant NRF2/HO-1 signaling in the eye d Itaconate treatment synergizes with antibiotics in ameliorating ocular infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…Because different pathogens cause experimental endophthalmitis at certain infectious doses ( Gupta et al., 2019 ; Francis et al., 2020 ; Kumar et al., 2020 ; Livingston et al., 2021 ), we performed a dose-response study beginning with an intravitreal injection of 5,000 cfu of S. epidermidis , a dose required for S. aureus endophthalmitis ( Singh et al., 2021 ). However, this inoculum was rapidly cleared from the mouse eyes resulting in transient inflammation (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because different pathogens cause experimental endophthalmitis at certain infectious doses ( Gupta et al., 2019 ; Francis et al., 2020 ; Kumar et al., 2020 ; Livingston et al., 2021 ), we performed a dose-response study beginning with an intravitreal injection of 5,000 cfu of S. epidermidis , a dose required for S. aureus endophthalmitis ( Singh et al., 2021 ). However, this inoculum was rapidly cleared from the mouse eyes resulting in transient inflammation (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Human RPE cells also exhibited a similar pattern of IL-1β and TNF-α mRNA ( Figure 7C ) and protein ( Figure 7D ) expression in response to S. epidermidis infection. PMNs and monocytes/macrophages are also major infiltrating innate immune cells during ocular infections ( Singh et al., 2021 ); therefore, we decided to assess the inflammatory response of mouse BMDMs. To this end, our data showed that S. epidermidis induced robust Il-6 and Cxcl1 mRNA ( Figure 7E ) and protein expressions ( Figure 7F ) in cultured BMDMs.…”
Section: Resultsmentioning
confidence: 99%
“…Because different pathogens cause experimental endophthalmitis at certain infectious doses (Gupta et al, 2019;Francis et al, 2020;Kumar et al, 2020;Livingston et al, 2021), we performed a doseresponse study beginning with an intravitreal injection of 5,000 cfu of S. epidermidis, a dose required for S. aureus endophthalmitis (Singh et al, 2021). However, this inoculum was rapidly cleared from the mouse eyes resulting in transient inflammation (data not shown).…”
Section: S Epidermidis Induces Endophthalmitis In B6 Mice At a Higher Infectious Dosementioning
confidence: 99%
“…Human RPE cells also exhibited a similar pattern of IL-1b and TNF-a mRNA (Figure 7C) and protein (Figure 7D) expression in response to S. epidermidis infection. PMNs and monocytes/ macrophages are also major infiltrating innate immune cells during ocular infections (Singh et al, 2021); therefore, we decided to assess the inflammatory response of mouse BMDMs. To this end, our data showed that S. epidermidis induced robust Il-6 and Cxcl1 mRNA (Figure 7E) and protein expressions (Figure 7F) in cultured BMDMs.…”
Section: S Epidermidis Induces the Production Of Inflammatory Mediators In Retinal Cellsmentioning
confidence: 99%
See 1 more Smart Citation